2010
DOI: 10.3390/ijms12010078
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Markers in Colorectal Cancer Prognosis

Abstract: The classification of colorectal cancers (CRC) is currently based largely on histologically determined tumour characteristics, such as differentiation status and tumour stage, i.e., depth of tumour invasion, involvement of regional lymph nodes and the occurrence of metastatic spread to other organs. These are the conventional prognostic factors for patient survival and often determine the requirement for adjuvant therapy after surgical resection of the primary tumour. However, patients with the same CRC stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 265 publications
1
42
0
2
Order By: Relevance
“…These data suggest that EpCAM+CD44+ may be used as a reliable marker of colorectal CSCs [16]. More importantly, scientists have demonstrated that the combined and sequential use of CSC markers led to higher purified CSC subpopulations than any single biomarker [43, 44]. To date, no study has investigated the characteristics of colorectal CSCs expressing Lgr5 combined with CD44 and EpCAM.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that EpCAM+CD44+ may be used as a reliable marker of colorectal CSCs [16]. More importantly, scientists have demonstrated that the combined and sequential use of CSC markers led to higher purified CSC subpopulations than any single biomarker [43, 44]. To date, no study has investigated the characteristics of colorectal CSCs expressing Lgr5 combined with CD44 and EpCAM.…”
Section: Discussionmentioning
confidence: 99%
“…It is the most frequent cancer after lung, breast, and ovarian cancer [2,3]. The disease occurs more commonly in the elderly population [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Biological markers, such as the DNA mismatch repair genes DCC, NM23-H1 and K-Ras have been verified as being able to predict disease relapse (7)(8)(9)(10). The application of those molecular markers at the clinical level remains limited, however, due to limitations in their reproducibility and independency from other major prognosticators.…”
Section: Introductionmentioning
confidence: 99%